The contribution of vocational training to employment, job-related skills and productivity: evidence from Madeira - Budría, Santiago (2021)
In this paper, we analyse the transition to the labor market of participants in vocational training in Madeira in Portugal. The analysis is in two stages. First, we investigate how the employ ment status at different dates (1 month, 1 year, and 2 years after the completion of the training program) depends on relevant variables, such as age, gender, education and the content and duration of the training. Second, we use individuals’ self assessment of the effectiveness of the training program along three dimensions: employment, job-related skills and produc tivity. The respondents score training activities high on every dimension. Moreover, we find that training is more effective among the educated, indicating that vocational training is far from being remedial. We also find that long training programs and training related to tourism are particularly effective.